Pathological and immunohistochemical effects of electromagnetic fields on rat liver - Cevik, A.; Aydin, M.; Timurkaan, N.; Apaydin, A. M.; Yuksel, M. (Agricultural Research Communication Centre, 2017)
The aim of this study was to investigate the possible effects of 50 Hz electromagnetic fields (EMFs) generated by high power lines on the morphology of rat liver and apoptosis. For this purpose, 28 adult male rats weighing 200-250 g were used. The treatment groups were kept in a shelter that were 7.5 m far from the high power lines carrying 170 kV (50 Hz) energy. The control animals (Group 1) were kept in an animal house where no electromagnetic fields were exposed. The animals of the groups 2, 3 and 4 were exposed to EMF (170 kV, 50 Hz) continously for 1, 2 and 3 months, respectively. At the end of the study periods, the animals were sacrificed and their livers were collected. Histopathological evaluation indicated that inflammatory cell infiltration localized in the portal areas was seen in the liver of experimental groups rats. Bax and Bcl-2 positive staining was observed in the liver of control and experimental groups, but both Bax and Bcl-2 staining was intense in Group 3. In conclusion, long-term exposure to EMFs may cause inflammatory changes and apoptosis in liver of rats.
Keywords: Bax; Bcl-2; Electromagnetic fields; Liver; Pathology; Rat